2013
DOI: 10.1111/jpi.12056
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves insulin sensitivity independently of weight loss in old obese rats

Abstract: In aged rats, insulin signaling pathway (ISP) is impaired in tissues that play a pivotal role in glucose homeostasis, such as liver, skeletal muscle, and adipose tissue. Moreover, the aging process is also associated with obesity and reduction in melatonin synthesis from the pineal gland and other organs. The aim of the present work was to evaluate, in male old obese Wistar rats, the effect of melatonin supplementation in the ISP, analyzing the total protein amount and the phosphorylated status (immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 72 publications
3
55
0
6
Order By: Relevance
“…However, similar to metformin, melatonin can increase the activity of AMPK and potentially enhance insulin sensitivity in the liver [101]. Accordingly, in aged rats, chronic melatonin supplementation in drinking water for 8-12 weeks increased insulin sensitivity by more than twofold without changing hepatic insulin receptor expression, suggesting that these insulin-sensitising effects were mediated by target tissues outside of the liver [102].…”
Section: Sleep Disturbance Circadian Disruption and Altered Glucose mentioning
confidence: 99%
“…However, similar to metformin, melatonin can increase the activity of AMPK and potentially enhance insulin sensitivity in the liver [101]. Accordingly, in aged rats, chronic melatonin supplementation in drinking water for 8-12 weeks increased insulin sensitivity by more than twofold without changing hepatic insulin receptor expression, suggesting that these insulin-sensitising effects were mediated by target tissues outside of the liver [102].…”
Section: Sleep Disturbance Circadian Disruption and Altered Glucose mentioning
confidence: 99%
“…Many studies have shown that melatonin has favorable effects on glucose homeostasis since it might increase glucose tolerance and improve insulin sensitivity in various animal models [32][33][34]. Melatonin administration has been shown to acutely decrease plasma insulin level and increase insulin sensitivity in rats [35].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is a hormone which is closely related to the regulation of insulin secretion and glucose/lipid metabolism. Melatonin showed positive impacts on metabolic syndrome due to its anti-hyperlipidemic effect and it is reported to reduce adiposity and body weight in animal studies (Chan & Tang, 1995;Srinivasan et al, 2013;Zanuto et al, 2013). Moreover, melatonin was showed to increase insulin sensitivity and glucose tolerance in rats fed with high fat or sucrose diets (Srinivasan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%